Preparation method and application of phosphorus-doped thiopolyacrylonitrile supported tin disulfide / ferrous disulfide composite electrode material for sodium ion battery
Patent Information
- Application Number
- CN202611010198.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-08
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-08
AI Technical Summary
In existing sodium-ion batteries, pure-phase SnS2 and FeS2 have low conductivity, slow ion kinetics, severe charge-discharge volume expansion and significant shuttle effect, which leads to electrode structure pulverization and mechanical degradation. Furthermore, there is a lack of effective strategies to improve the conductivity and conversion reaction kinetics of SPAN.
A method for preparing phosphorus-doped thiopolyacrylonitrile-supported tin disulfide/ferrous disulfide composite electrode material was adopted. SnS2/FeS2 heterojunction was formed by solvothermal method combined with annealing treatment, and spontaneous growth was carried out on P-SPAN substrate to build a built-in electric field to suppress polysulfide shuttle effect and enhance structural stability and conductivity.
It achieves high electrochemical performance and ultra-long cycle life over a wide temperature range. The material exhibits excellent electrochemical performance in the range of -50℃ to 60℃. It retains a capacity of 201.35mAh g⁻¹ after 10,000 cycles at a current density of 30A g⁻¹ at room temperature. It has high reversible capacity at low temperatures and stable capacity at high temperatures, which significantly improves the electrochemical performance and cycle stability of sodium-ion batteries.
Smart Images

Figure CN122532217B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of sodium-ion batteries, and in particular to a method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries and its application. Background Technology
[0002] To date, researchers have ingeniously designed various electrode materials for use as anodes in SIBs. Transition metal sulfides (TMSs) are highly competitive in the field of novel energy storage due to their abundant reversible redox reactions, good reversibility, and easily tunable morphology. Pyrite-type ferrous disulfide (FeS2), a transition metal sulfide, is naturally occurring, possesses good thermal stability, is non-toxic, and has a theoretical capacity of up to 894 mAh g⁻¹. - ¹ is a highly promising candidate material for sodium storage; it can transfer sodium to the highly conductive metallic phase Na during the initial cycle. x The FeS2 transformation effectively promotes the reversible insertion / extraction of sodium ions. Tin disulfide (SnS2) has a layered crystal structure, with S-Sn-S atomic layers stacked by van der Waals forces, and a layer spacing of 0.59 nm along the c-axis, possessing rapid ion diffusion kinetics and efficient sodium ion transport channels; moreover, conversion and alloying reactions accompany the sodium storage process, with a theoretical capacity as high as 1136 mAh g⁻¹. - ¹. Despite the many advantages mentioned above, both pure-phase SnS2 and FeS2 share common problems such as low intrinsic conductivity, slow ion dynamics, severe charge-discharge volume expansion, and significant shuttle effect. These issues can easily lead to electrode structure pulverization and mechanical decay, resulting in actual capacities that are far lower than theoretical values.
[0003] To address the aforementioned bottlenecks, constructing heterojunction structures by combining SnS2 and FeS2 has become an effective strategy for optimizing the electrochemical performance of materials. By rationally controlling the preparation process, SnS2 nanosheets and FeS2 particles can form SnS2 / FeS2 heterojunctions. This unique interfacial structure offers multiple synergistic advantages, enhancing the structural stability of the material during charge and discharge processes. This provides a reliable structural design approach for developing high-performance SIB anode materials.
[0004] However, while heterostructures can alleviate the volume effect, they cannot effectively suppress the sodium polysulfide (NaPSs) shuttle effect caused by the side reactions of metal sulfides and electrolytes—this remains another core factor leading to low battery coulombic efficiency and capacity decay.
[0005] Typically, nonpolar carbon matrices exhibit weak chemisorption of polysulfides and limited ability to suppress the dissolution-shuttle effect. Interestingly, under specific conditions, sulfurized polyacrylonitrile (SPAN) matrices follow a unique solid-solid conversion mechanism, effectively eliminating the polysulfide shuttle problem. However, SPAN's inherently unsatisfactory ionic / electronic conductivity and conversion kinetics limit its practical application. Unfortunately, to date, an effective strategy to simultaneously improve SPAN conductivity, cycle stability, and conversion kinetics remains lacking. Furthermore, research on improving SPAN conversion kinetics in sodium-ion battery systems over a wide temperature range is scarce.
[0006] In view of this, the inventor of this case conducted in-depth research, which led to the creation of this case. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries with good electrochemical performance and cycle life.
[0008] Another objective of this invention is to provide an application of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries, which has good electrochemical performance and cycle life.
[0009] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries includes the following steps: Step 1, Preparation of precursors: Fe(NO3)3·9H2O and SnCl2·5H2O were added sequentially to 100 mL of deionized water, stirred to dissolve, and then ultrasonically vibrated for 0.5 to 1 hour to obtain a uniformly dispersed solution. Then, thiourea was added to 50 mL of deionized water, stirred and dissolved, and then mixed evenly with the uniformly dispersed solution. The mixture was transferred to a reaction vessel and kept at 150-200℃ for 3-4 hours. The resulting precipitate was washed alternately with ethanol and deionized water, and then dried in a vacuum drying oven at 60-80℃ to obtain the SnS2 / FeS2 precursor. Step 2, Carbonization: Spirulina powder was carbonized in a nitrogen atmosphere, heated to 600°C at a heating rate of 3-5°C / min, held at that temperature for 2-4 hours, and then cooled to room temperature to obtain phosphorus-containing carbon powder. Step 3, vulcanization and compounding: The precursor obtained in step 1, the phosphorus-containing carbon powder and sulfur powder obtained in step 2, and polyacrylonitrile were mixed, ground for 20 minutes, ethanol was added, ball milled for 10-12 hours, and then vacuum dried at 60°C. The dried powder was first kept at 150-160℃ for 160-200 minutes under a nitrogen atmosphere for the first stage of heat preservation, and then the temperature was raised to 350-400℃ and kept for 200-270 minutes for the second stage of heat preservation. After cooling to room temperature, a black powder was obtained, which is the target product SnS2 / FeS2-P-SPAN.
[0010] Further, in step 1, the mass ratio of Fe(NO3)3•9H2O to SnCl2•5H2O is 1:1~2.
[0011] Further, in step 1, the mass ratio of thiourea to Fe(NO3)3•9H2O is 1~4:1.
[0012] Further, in step 1, the mass ratio of thiourea to SnCl2•5H2O is 1~2:1.
[0013] Furthermore, in step 2, the mass ratio of sulfur powder to SnS2 / FeS2 is 1:1 to 1:2.
[0014] Furthermore, in step 3, the mass ratio of PAN to SnS2 / FeS2 is 1:1 to 4:1.
[0015] Furthermore, in step 3, the heating rate is 3°C / min.
[0016] Furthermore, the ultrasonic vibration time in step 1 is 0.5 hours or 1 hour; the heat preservation temperature in the reaction vessel is 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃, and the heat preservation time is 3 hours or 4 hours. The heating rate in step 2 is 3℃ / min, 4℃ / min or 5℃ / min, and the carbonization holding time is 2 hours, 3 hours or 4 hours; The ball milling time in step 3 is 10 hours, 11 hours or 12 hours, the first stage heat preservation temperature is 150℃, 155℃ or 160℃, the first stage heat preservation time is 160 minutes, 180 minutes or 200 minutes, the second stage heat preservation temperature is 350℃, 375℃ or 400℃, and the second stage heat preservation time is 200 minutes, 230 minutes or 270 minutes.
[0017] An application of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries, wherein the SnS2 / FeS2-P-SPAN is used to prepare a negative electrode sheet for sodium-ion batteries. The preparation method of the negative electrode sheet for sodium-ion batteries includes the following steps: first, the SnS2 / FeS2-P-SPAN, conductive agent and binder are mixed evenly in a mass ratio of 7~8:1~2:1~2, solvent is added to prepare a slurry, and the slurry is ball-milled in a planetary ball mill for 6~8 hours. Then, the obtained slurry is evenly coated on copper foil and vacuum dried at 60~80℃ for 10~12 hours to obtain the negative electrode sheet for sodium-ion batteries.
[0018] Furthermore, the conductive agent is Super P, the adhesive is PVDF, and the solvent is NMP.
[0019] After adopting the above technical solution, the preparation method of the phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries of the present invention has the following beneficial effects: A simple solvothermal method combined with annealing is used to form a SnS2 / FeS2 bimetallic heterojunction precursor during hydrothermal processing. Subsequently, during sulfidation, the SnS2 / FeS2 heterojunction spontaneously grows on the surface of a P-SPAN substrate to form a composite electrode material, which has the following beneficial effects: 1. Due to the formation of SnS2 / FeS2 heterojunction, the active material is transformed into three-dimensional nanosheets with more uniform size. At the same time, these three-dimensional nanosheets spontaneously and uniformly grow on the P-SPAN substrate, which greatly increases the specific surface area of the material, exposes more active sites, and is conducive to the redox reaction. 2. P-doped SPAN can alleviate the severe volume expansion of SnS2 / FeS2 nanosheets during the charge-discharge reaction process. Furthermore, P-SPAN exhibits a "solid-solid transformation" mechanism under specific conditions, which can suppress the formation of polysulfides at the source, thus helping to suppress the shuttle effect, further enhancing structural stability, and improving the structural toughness of the electrode material, thereby achieving ultra-long cycle life and cycle stability over a wide temperature range. 3. SnS2 and FeS2 differ in their band structures and Fermi levels. Upon contact, spontaneous migration of interfacial charges occurs, leading to the formation of a directional built-in electric field. The successful construction of this built-in electric field effectively reduces the transport resistance of sodium ions and accelerates their transport, while suppressing charge accumulation at the interface, resulting in a fast reaction kinetics for the anode.
[0020] Applying this composite electrode material to the anode of sodium-ion batteries enables the batteries to have an ultra-wide operating temperature range (-50℃~60℃). P doping effectively enhances the conductivity of the SPAN substrate, improves charge transfer kinetics, and simultaneously enhances the adsorption capacity for charge-discharge products during cycling. The SnS2 / FeS2 heterostructure establishes a built-in electric field, accelerating ion transport and mitigating volume expansion. The P-SPAN matrix suppresses the shuttle effect of polysulfides through a solid-solid conversion mechanism, enhancing structural stability.
[0021] Multiple synergistic effects enable the material to exhibit excellent electrochemical performance over a wide temperature range of -50 to 60 °C and at high rates.
[0022] At room temperature, this material at 30 A g - ¹ It retains 201.35 mAh g⁻¹ even after 10,000 cycles at an ultra-high current density. - ¹ Capacity; at low temperatures, the reversible capacity reaches 286.48 mAh g at -40 ℃. - ¹, After 100 cycles at -50 ℃, the capacity is 231.70 mAh g. - ¹; Under high temperature conditions, 60 ℃, 2 Ag - ¹ Under these conditions, after 1000 cycles, the energy content remains at 588.65 mAh g. - ¹. This material also exhibits excellent rate performance.
[0023] This paper proposes a green phosphorus doping strategy to improve the conversion reaction kinetics and intrinsic conductivity of SPAN materials in wide-temperature-range sodium-ion batteries, which has important research significance and application value.
[0024] This invention provides a new approach to suppressing shuttle effect and volume expansion by constructing a heterogeneous interface and combining it with a phosphorus-doped SPAN substrate, and offers a feasible strategy for high-power, long-life, and wide-temperature-range sodium-ion battery anodes. Attached Figure Description
[0025] Figure 1 SEM images of SnS2 / FeS2-P-SPAN, SnS2-P-SPAN, FeS2-P-SPAN, and SnS2 / FeS2-SPAN prepared in Example 1 and Comparative Examples 1 to 3, respectively. in, Figure 1 a corresponds to SnS2 / FeS2-P-SPAN (Example 1). Figure 1 b corresponds to SnS2-P-SPAN (Comparative Example 1). Figure 1 c corresponds to FeS2-P-SPAN (Comparative Example 2). Figure 1d corresponds to SnS2 / FeS2-SPAN (Comparative Example 3); Figure 2 The characterization results are for the SnS2 / FeS2-P-SPAN prepared in Example 1. in, Figure 2 a and Figure 2 b shows scanning electron microscope (SEM) images of SnS2 / FeS2-P-SPAN at different magnifications; Figure 2 c is the EDS (energy dispersive spectroscopy) diagram of SnS2 / FeS2-P-SPAN; Figure 3 TEM image of SnS2 / FeS2-P-SPAN prepared in Example 1; in, Figure 3 a is a transmission electron microscope (TEM) morphology image; Figure 3 b is a high-resolution TEM image, showing clear lattice fringes with interplanar spacings of 0.278 nm and 0.27 nm, corresponding to the (101) plane of SnS2 and the (200) plane of FeS2, respectively. Figure 3 c is Figure 3 A magnified view of part b.
[0026] Figure 4 The XRD patterns of SnS2 / FeS2-P-SPAN, SnS2-P-SPAN, FeS2-P-SPAN, and SnS2 / FeS2-SPAN prepared in Example 1 and Comparative Examples 1 to 3 are shown. in, Figure 4 a corresponds to SnS2 / FeS2-P-SPAN (Example 1). Figure 4 b corresponds to SnS2-P-SPAN (Comparative Example 1). Figure 4 c corresponds to FeS2-P-SPAN (Comparative Example 2). Figure 4 d corresponds to SnS2 / FeS2-SPAN (Comparative Example 3).
[0027] Figure 5 The rate performance comparison chart shows the SnS2 / FeS2-P-SPAN prepared in Example 1 and Comparative Examples 1 to 3 respectively. in, Figure 5 Performance comparison chart of g-1 with a value of 0.1 A. Figure 5 b is a performance comparison chart of A g-1.
[0028] In each figure, SnS2 / FeS2-P-SPAN corresponds to Example 1, SnS2-P-SPAN corresponds to Example 1, FeS2-P-SPAN corresponds to Example 2, and SnS2 / FeS2-SPAN corresponds to Example 3. Figure 6 The comparison chart shows the cycling performance of SnS2 / FeS2-P-SPAN prepared in Example 1 and Comparative Examples 1 to 3 respectively. Among them, SnS2 / FeS2-P-SPAN corresponds to Example 1, SnS2-P-SPAN corresponds to Example 1, FeS2-P-SPAN-3 corresponds to Example 2, and SnS2 / FeS2-SPAN corresponds to Example 3. Figure 7 The SnS2 / FeS2-P-SPAN prepared in Example 1 was subjected to a current density of 20 A g. -1 and 30 A g -1 The following is a graph showing the cyclic performance. Figure 8 The SnS2 / FeS2-P-SPAN prepared in Example 1 exhibited a current density of 0.2 A g at -40°C and -50°C. -1 The following is a graph showing the cyclic performance. Figure 9 The SnS2 / FeS2-P-SPAN prepared in Example 1 exhibited a current density of 2 Ag at 50°C and 60°C. -1 The following is a graph showing the cyclic performance. Detailed Implementation
[0029] I. Preparation of Composite Electrode Materials Example 1 This invention discloses a method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material (hereinafter referred to as SnS2 / FeS2-P-SPAN) for sodium-ion batteries, comprising the following steps: Step 1, Precursor Preparation: First, add 1g of Fe(NO3)3•9H2O and 1-2g of SnCl2•5H2O to 100mL of deionized water and stir to dissolve. Then, sonicate for 0.5-1 hour to ensure uniform dispersion and obtain a homogeneous solution. Next, add 1-4g of thiourea (NS) to 50mL of deionized water and stir to dissolve. Mix this solution thoroughly with the homogeneous solution obtained after sonication and transfer it to a reaction vessel. Incubate at 150-200℃ for 3-4 hours. Wash the resulting precipitate several times alternately with ethanol and deionized water. Then, dry the washed precipitate overnight in a vacuum drying oven at 60-80℃ to obtain the SnS2 / FeS2 precursor. Step 2, Carbonization: The washed and dried spirulina powder was carbonized in a nitrogen atmosphere at a heating rate of 3-5℃ / min. After heating to 600℃ for 2-4 hours, it was cooled to room temperature and then taken out for use to obtain phosphorus-containing carbon powder. Step 3, vulcanization: Then, the precursor obtained in step 1, the phosphorus-containing carbon powder obtained in step 2, sulfur powder, and polyacrylonitrile (PAN) were mixed and ground for 20 minutes. The mass ratio of phosphorus-containing carbon powder to precursor was 1:0.5, the mass ratio of sulfur powder to precursor was 1:1~2, and the mass ratio of PAN to precursor was 1~4:1. Subsequently, an appropriate amount of ethanol was added, and the mixture was transferred to a ball mill and ball-milled for 10-12 hours. Then, it was vacuum-dried overnight at 60°C. The dried powder was then heated at 150~160°C for 160~200 min under a nitrogen atmosphere for the first stage of heating, and then heated to 350~400°C for 200~270 min for the second stage of heating. After cooling to room temperature, the powder was removed, and the resulting black powder was the target product SnS2 / FeS2-P-SPAN.
[0030] In this invention, in step 1, the mass ratio of Fe(NO3)3•9H2O to SnCl2•5H2O is 1:1~2; In step 1, the mass ratio of NS to Fe(NO3)3•9H2O is 1~4:1; In step 1, the mass ratio of NS to SnCl2•5H2O is 1~2:1; In step 3, the mass ratio of sulfur powder to SnS2 / FeS2 (precursor) is 1:1 to 1:2; In step 3, the mass ratio of PAN to SnS2 / FeS2 (precursor) is 1:1 to 4:1.
[0031] Comparative Example 1 Compared with Example 1, in the preparation of the precursor in step 1, only SnCl2•5H2O was added, and Fe(NO3)3•9H2O was not added.
[0032] A method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide composite electrode material (hereinafter referred to as SnS2-P-SPAN) for sodium-ion batteries includes the following steps: Step 1, Precursor Preparation: First, add 1-2 g of SnCl2•5H2O to 100 mL of deionized water and stir to dissolve. Then, sonicate for 0.5-1 hour to disperse the solution evenly. Then, add 1-4 g of NS to 50 mL of deionized water and stir to dissolve. Mix the solution with the dispersion solution after sonication and transfer it to a reaction vessel. Keep the mixture at 150-200℃ for 3-4 hours. Wash the precipitate with ethanol and deionized water several times alternately. Then, place the washed precipitate in a vacuum drying oven at 60-80℃ and dry it overnight to obtain the SnS2 precursor. Step 2, Carbonization: The washed and dried spirulina powder was carbonized in a nitrogen atmosphere at a heating rate of 3-5℃ / min. After heating to 600℃ for 2-4 hours, it was cooled to room temperature and then taken out for use to obtain phosphorus-containing carbon powder. Step 3, vulcanization: Then, the precursor obtained in step 1, the phosphorus-containing carbon powder obtained in step 2, the sulfur powder, and PAN are mixed and ground for 20 minutes. The mass ratio of phosphorus-containing carbon powder to precursor is 1:0.5, the mass ratio of sulfur powder to precursor is 1:1~2, and the mass ratio of PAN to precursor is 1~4:1. Subsequently, an appropriate amount of ethanol is added, and the mixture is transferred to a ball mill and ball-milled for 10-12 hours. Then, it is vacuum-dried overnight at 60°C. The dried powder is then heated at 150~160°C for 160~200 min under a nitrogen atmosphere, then heated to 350~400°C and held for 200~270 min. After cooling to room temperature, the resulting black powder is the target product SnS2-P-SPAN.
[0033] Comparative Example 2 The difference between this comparative example and Example 1 is that only Fe(NO3)3•9H2O was added in the preparation of the precursor in step 1, and SnCl2•5H2O was not added.
[0034] A method for preparing a phosphorus-doped thiopolyacrylonitrile-supported ferrous disulfide composite electrode material (hereinafter referred to as FeS2-P-SPAN) for sodium-ion batteries includes the following steps: A method for preparing a phosphorus-doped thiopolyacrylonitrile-supported ferrous disulfide composite electrode material (hereinafter referred to as FeS2-P-SPAN) for sodium-ion batteries includes the following steps: Step 1, Precursor Preparation: First, add 1 g of Fe(NO3)3•9H2O to 100 mL of deionized water and stir to dissolve. Then, sonicate for 0.5-1 hour to disperse the solution evenly and obtain a homogeneous solution. Next, add 1-4 g of NS to 50 mL of deionized water and stir to dissolve. Mix the solution with the dispersion solution after sonication and transfer it to a reaction vessel. Keep the mixture at 150-200℃ for 3-4 hours. Wash the precipitate several times with ethanol and deionized water alternately. Then, place the washed precipitate in a vacuum drying oven at 60-80℃ and dry it overnight to obtain the precursor of FeS2. Step 2, Carbonization: The washed and dried spirulina powder was carbonized in a nitrogen atmosphere at a heating rate of 3-5℃ / min. After heating to 600℃ for 2-4 hours, it was cooled to room temperature and then taken out for use to obtain phosphorus-containing carbon powder. Step 3, vulcanization: Then, the precursor obtained in step 1, the phosphorus-containing carbon powder obtained in step 2, the sulfur powder, and PAN are mixed and ground for 20 minutes. The mass ratio of phosphorus-containing carbon powder to precursor is 1:0.5, the mass ratio of sulfur powder to precursor is 1:1~2, and the mass ratio of PAN to precursor is 1~4:1. Subsequently, an appropriate amount of ethanol is added, and the mixture is transferred to a ball mill and ball-milled for 10-12 hours. Then, it is vacuum-dried overnight at 60°C. The dried powder is then heated at 150~160°C for 160~200 min under a nitrogen atmosphere, then heated to 350~400°C and held for 200~270 min. After cooling to room temperature, the resulting black powder is the target product FeS2-P-SPAN.
[0035] Comparative Example 3 The difference between this comparative example and Example 1 is that it was not p-doped.
[0036] A method for preparing a thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material (hereinafter referred to as SnS2 / FeS2-SPAN) for sodium-ion batteries includes the following steps: Step 1, Precursor Preparation: First, add 1 g of Fe(NO3)3•9H2O and 1~2 g of SnCl2•5H2O to 100 mL of deionized water and stir to dissolve. Then, sonicate for 0.5-1 hour to disperse the solution evenly and obtain a homogeneous solution. Next, add 1~4 g of NS to 50 mL of deionized water and stir to dissolve. Mix the solution with the dispersion obtained after sonication and transfer it to a reaction vessel. Keep it at 150~200℃ for 3~4 hours. Wash the obtained precipitate several times with ethanol and deionized water alternately. Then, place the washed precipitate in a vacuum drying oven at 60~80℃ and dry it overnight to obtain the SnS2 / FeS2 precursor. Step 2, vulcanization: The precursor obtained in step 1 is then mixed with sulfur powder and PAN, and ground for 20 minutes. The mass ratio of sulfur powder to precursor is 1:1~2, and the mass ratio of PAN to precursor is 1~4:1. An appropriate amount of ethanol is then added, and the mixture is transferred to a ball mill and ball-milled for 10-12 hours. The mixture is then vacuum-dried overnight at 60°C. The dried powder is then heated at 150~160°C for 160~200 min under a nitrogen atmosphere, then heated to 350~400°C and held for 200~270 min. After cooling to room temperature, the resulting black powder is the target product SnS2 / FeS2-SPAN.
[0037] II. Applications of Composite Electrode Materials The electrode materials prepared in Examples 1 to 3 were used to prepare negative electrode sheets for sodium-ion batteries.
[0038] The preparation method of various negative electrode sheets for sodium-ion batteries includes the following steps: First, the electrode material, conductive agent conductive carbon black (Super P) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of (8~7):(2~1):1. Then, 800~1000 μL of solvent N-methylpyrrolidone (NMP) is added to each 0.2g of mixed material to prepare a slurry. The slurry is then ball-milled in a planetary ball mill for 8 hours. Finally, the prepared slurry is evenly coated on copper foil and vacuum dried at 80°C for 12 hours to obtain the negative electrode sheet for sodium-ion batteries.
[0039] III. Characterization of Composite Electrode Materials 1. Figure 1 The image shows a SEM image of the SnS2 / FeS2-P-SPAN prepared in Example 1. The image clearly shows that SnS2 / FeS2 nanosheets are uniformly distributed on the surface of the P-SPAN.
[0040] 2. Figure 2 The image shows the EDS image of SnS2 / FeS2-P-SPAN prepared in Example 1. The image shows the presence of C, Fe, Sn, S, P and N elements, and that each element is uniformly distributed on the P-SPAN substrate.
[0041] 3. Figure 3 The image shows a TEM image of the SnS2 / FeS2-P-SPAN prepared in Example 1. The image shows that the lattice spacing of the SnS2 (101) crystal plane is 2.78 Å and the lattice spacing of the FeS2 (200) crystal plane is 2.71 Å. The two phases form a clear heterojunction interface, indicating the successful construction of the bimetallic sulfide heterojunction interface.
[0042] 4. Figure 4The images show the XRD patterns of SnS2 / FeS2-P-SPAN, SnS2-P-SPAN, FeS2-P-SPAN, and SnS2 / FeS2-SPAN prepared in Example 1 and Comparative Examples 1 to 3, respectively. Figure 4 Image a shows the XRD pattern of SnS2 / FeS2-P-SPAN. All diffraction peaks originate from the standard spectra of pyrite phase FeS2 and Berndtite-2T phase SnS2, showing high agreement. This indicates the successful preparation of the SnS2 / FeS2 heterojunction. For the SnS2-P-SPAN prepared in Comparative Example 1 (…),… Figure 4 b) and FeS2-P-SPAN prepared in Comparative Example 2 ( Figure 4 c), all peak signals highly matched the standard spectra of Berndtite-2T phase SnS2 and pyrite phase FeS2, and no diffraction peaks matching the relevant impurities were detected. In contrast, the SnS2 / FeS2-SPAN prepared in Comparative Example 3 ( Figure 4 d) All diffraction peaks also originate from the peak signals of FeS2 and SnS2.
[0043] IV. Performance Testing of Composite Electrode Materials 1. Figure 5 The rate performance diagrams are for SnS2 / FeS2-P-SPAN, SnS2-P-SPAN, FeS2-P-SPAN and SnS2 / FeS2-SPAN prepared in Example 1 and Comparative Examples 1 to 3 respectively.
[0044] in, Figure 5 a is in 0.1 A g - ¹Comparison of cycling performance at current density Figure 5 b is in 1 A g - ¹Comparison of cycling performance at current densities. As shown in the figure, the SnS2 / FeS2-P-SPAN prepared in Example 1 exhibits the highest specific capacity and excellent cycling stability compared to the comparative examples at both current densities. Its capacity retention is significantly better than that of the comparative examples, indicating that the synergistic effect of phosphorus doping and the SnS2 / FeS2 heterostructure effectively improves the electrochemical performance of the material. The good rate performance can be attributed to the built-in electric field at the SnS2 / FeS2 heterostructure interface and the phosphorus doping jointly accelerating the transport rate of sodium ions in the reaction.
[0045] 2. Figure 6The graph shows a comparison of the cycling performance of SnS2 / FeS2-P-SPAN, SnS2-P-SPAN, FeS2-P-SPAN, and SnS2 / FeS2-SPAN prepared in Example 1 and Comparative Examples 1 to 3. As can be seen from the graph, the SnS2 / FeS2-P-SPAN corresponding to Example 1 has the highest reversible capacity.
[0046] 3. Figure 7 The SnS2 / FeS2-P-SPAN prepared in Example 1 was subjected to an ultra-high current density of 20 Ag. - ¹ and 30Ag - ¹Long-term cycling tests were conducted. At a current density of 20 A g⁻¹, the coulombic efficiency was 71.85% in the first cycle, and approached 100% after activation. After 10,000 cycles, the SnS₂ / FeS₂-P-SPAN still provided 251.19 mAh g⁻¹. -1 The reversible capacity was maintained at 85.1%, with a capacity decay of only 0.0014% per cycle. The current density was then increased to 30 A g. -1 After activation, the coulombic efficiency is close to 100%, and after 10,000 cycles, it still provides a reversible capacity of 201.38 mAh g⁻¹. The ultra-long stable cycling of the SnS₂ / FeS₂-P-SPAN electrode material under the aforementioned high current is due to the three-dimensional sheet structure of SnS₂ / FeS₂, which effectively alleviates the volume expansion of the electrode material during charge and discharge. In addition, due to the high conductivity and supporting effect of the P-SPAN substrate, it can effectively support the three-dimensional sheet-like active material. At the same time, due to the unique "solid-solid conversion mechanism" of P-SPAN, it can effectively suppress the shuttle effect of polysulfides, resulting in an ultra-long cycle life. These synergistic effects of multiple aspects enable the material to have excellent rate performance and outstanding cycle stability even under high current.
[0047] 4. Figure 8 and Figure 9 The SnS2 / FeS2-P-SPAN prepared in Example 1 underwent long-term cycling tests at high and low temperatures, demonstrating that the battery could withstand extremely low temperatures of -40°C and -50°C with a current density of 0.2 A g⁻¹. Figure 8 After 100 cycles, the battery still provides reversible capacities of 286.48 mAh g⁻¹ and 231.70 mAh g⁻¹, respectively. It can still operate at a high temperature of 50°C, with the battery operating at 2A g⁻¹. -1 After cycling 1000 times at a current density, it still provides a reversible capacity of over 543.1 mAh g⁻¹; even at an ultra-high temperature of 60°C, it still provides a reversible capacity of over 588.65 mAh g⁻¹. Figure 9 ).
[0048] Therefore, this paper presents a method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries. The prepared phosphorus-doped thiopolyacrylonitrile-supported tin disulfide composite electrode material improves the long-cycle stability and feasibility of the battery under high and low temperature environments.
[0049] The above embodiments and accompanying drawings are not intended to limit the product form and style of the present invention. Any appropriate changes or modifications made by those skilled in the art should be considered as not departing from the patent scope of the present invention.
Claims
1. A method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries, characterized in that, Includes the following steps: Step 1, Preparation of precursors: Fe(NO3)3·9H2O and SnCl2·5H2O were added sequentially to 100 mL of deionized water, stirred to dissolve, and then ultrasonically vibrated for 0.5 to 1 hour to obtain a uniformly dispersed solution. Then, thiourea was added to 50 mL of deionized water, stirred and dissolved, and then mixed evenly with the uniformly dispersed solution. The mixture was transferred to a reaction vessel and kept at 150-200℃ for 3-4 hours. The resulting precipitate was washed alternately with ethanol and deionized water, and then dried in a vacuum drying oven at 60-80℃ to obtain the SnS2 / FeS2 precursor. Step 2, Carbonization: Spirulina powder was carbonized in a nitrogen atmosphere, heated to 600°C at a heating rate of 3-5°C / min, held at that temperature for 2-4 hours, and then cooled to room temperature to obtain phosphorus-containing carbon powder. Step 3, vulcanization and compounding: The SnS2 / FeS2 precursor obtained in step 1, the phosphorus-containing carbon powder, sulfur powder and polyacrylonitrile obtained in step 2 are mixed, ground for 20 minutes, ethanol is added, ball milling is performed for 10-12 hours, and then vacuum drying is carried out at 60°C. The dried powder was first kept at 150-160℃ for 160-200 minutes under a nitrogen atmosphere as the first stage of heat preservation, and then the temperature was raised to 350-400℃ and kept for 200-270 minutes as the second stage of heat preservation. After cooling to room temperature, a black powder was obtained. This black powder is the target product SnS2 / FeS2-P-SPAN, in which SnS2 / FeS2 nanosheets are uniformly distributed on the surface of P-SPAN.
2. The preparation method of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in claim 1, characterized in that: In step 1, the mass ratio of Fe(NO3)3•9H2O to SnCl2•5H2O is 1:1~2.
3. The preparation method of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in claim 1, characterized in that: In step 1, the mass ratio of thiourea to Fe(NO3)3•9H2O is 1:1 to 4:
1.
4. The preparation method of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in claim 1, characterized in that: In step 1, the mass ratio of thiourea to SnCl2•5H2O is 1~2:
1.
5. The method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries according to claim 1, characterized in that: In step 3, the mass ratio of sulfur powder to SnS2 / FeS2 precursor is 1:1 to 1:
2.
6. The method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries according to claim 1, characterized in that: In step 3, the mass ratio of the polyacrylonitrile to the SnS2 / FeS2 precursor is 1:1 to 4:
1.
7. The method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries according to claim 1, characterized in that: In step 3, the heating rate is 3°C / min.
8. The method for preparing a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries according to claim 1, characterized in that: The ultrasonic vibration time in step 1 is 0.5 hours or 1 hour; the heat preservation temperature in the reaction vessel is 150℃, 160℃, 170℃, 180℃, 190℃ or 200℃, and the heat preservation time is 3 hours or 4 hours. The heating rate in step 2 is 3℃ / min, 4℃ / min, or 5℃ / min, and the carbonization holding time is 2 hours, 3 hours, or 4 hours; the ball milling time in step 3 is 10 hours, 11 hours, or 12 hours, the first holding temperature is 150℃, 155℃, or 160℃, and the first holding time is 160 minutes, 180 minutes, or 200 minutes; the second holding temperature is 350℃, 375℃, or 400℃, and the second holding time is 200 minutes, 230 minutes, or 270 minutes.
9. An application of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries, characterized in that: SnS2 / FeS2-P-SPAN obtained by the preparation method of phosphorus-doped thiopolyacrylonitrile supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in any one of claims 1 to 8 will be used to prepare negative electrode sheets for sodium-ion batteries. The method for preparing the negative electrode sheet for sodium-ion batteries includes the following steps: SnS2 / FeS2-P-SPAN, a conductive agent, and a binder obtained by the preparation method of a phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in any one of claims 1 to 8 are mixed evenly at a mass ratio of 7 to 8: 1 to 2: 1 to 2. A solvent is added to prepare a slurry, which is then ball-milled in a planetary ball mill for 6 to 8 hours. The slurry is then uniformly coated onto a copper foil and vacuum-dried at 60 to 80°C for 10 to 12 hours to obtain the negative electrode sheet for sodium-ion batteries.
10. The application of the phosphorus-doped thiopolyacrylonitrile-supported tin disulfide / ferrous disulfide composite electrode material for sodium-ion batteries as described in claim 9, characterized in that: The conductive agent is Super P, the adhesive is PVDF, and the solvent is NMP.
Citation Information
Patent Citations
Method for the production of a polyacrylonitrile-sulfur composite material
CN104334613A
Preparation method and application of sulfur-doped polyacrylonitrile-chlorella derived carbon compound sodium ion battery negative electrode material
CN113823782A
